IS (Islamic State) and the Pakistani Ṭālibān: Historical Back Ground, Similarities and Allegiances (Al-Qamar, 2020)
The new concept of “Islamic State (IS)” is as old as human history itself; and it has been a subject of discussion both academically and non-academically or even socially. This article examines the impact of the concept of IS on religious extremism in Muslim countries and Pakistan in particular. It discusses the alliance between the IS and the Pakistani Ṭālibān and examines its historical dimensions. It is pointed out that Pakistan is not a fertile land for the religious extremism as it is war-torn territories of the Levant. It is argued that IS and the Pakistani Ṭālibān remnants have aligned themselves with other splinter groups. Thus, the Pakistani Ṭālibān and IS understand each other and mutually express their allegiances. It is also argued that the IS phenomenon is an ideological war that finds its own place where there are ideological harmony and geographical resemblances. However, the IS ideology has no grassroots support but the Pakistani Ṭālibān ideology does. Yet, both ideologies are the denizens of the other organizations. They are supporters, facilitators, and financiers for each other. It is concluded that the IS is a weaker partner to the Pakistani Ṭālibān.
Keywords: Islamic State; Taliban, Ideologies; Resurrection; Extremism; Resemblance